PROSES MORFOLOGIS DALAM BAHASA MINANG DIALEK SIMPANG EMPAT DI PASAMAN BARAT - Oktaviana, Muna (University of Brawijaya, 2022)
This study aims to describe and determine the form, function and meaning that occurs in the morphological process of the Minang language in Simpang Empat, West Pasaman. In analyzing the data, this study used a qualitative descriptive method. Data in Minang language translated into Indonesian. The function and meaning of prefixes, infixes, and suffixes in the study of morphological processes. This is the basis for research that departs to describe the measuring data used.There are forms of processes and meanings in morphological studies that include prefixes, suffixes, and infixes in the Minang language. There are four types of affixes in Minang language, namely ba-, man-, pa-, di, ka-, ta-, -an, di-an, ba-an, pan-an, and ka-an. The meaning of the affix will be formed according to the affix attached to the root word. The function of affixes in the Minang language is to change the type of word from other types of words.